Oxytocin blood concentrations in alcohol use disorder: A cross-sectional, longitudinal, and sex-separated study - Lenz, Bernd; Weinland, Christian; Bach, Patrick; Kiefer, Falk; Grinevich, Valery; Zoicas, Iulia; Kornhuber, Johannes; Mühle, Christiane (European Neuropsychopharmacology, 2021)
Alcohol use disorder (AUD) is a severe illness, for which we lack sufficient mechanistic understanding. Preliminary evidence associates AUD with the oxytocin (OXT) system. Here we investigated alterations in endogenous OXT blood concentrations in patients with AUD and their association with alcohol drinking and prospective course. In sex-separated analyses, OXT serum concentrations of 200 in-patients with AUD (56.5% male; baseline, 24–72 h of abstinence) were compared with those of 240 age-matched healthy controls (55.4% male), investigated longitudinally (follow-up, 5 days later), and tested for associations with alcohol drinking behavior and prospective 24-month alcohol-related hospital readmissions. At baseline, the patients showed increased OXT concentrations relative to controls (men, 156%, P < 0.001; women, 124%, P = 0.002). The elevations normalized at follow-up. In male patients, baseline OXT concentrations correlated positively with alcohol concentration at admission, the amount of alcohol consumption per drinking year, and the number of previous withdrawal treatments (Rho > 0.195, P < 0.044). In beverage type-specific analysis, baseline OXT concentrations correlated with liquor consumption positively in male and negatively in female patients (|Rho| > 0.277, P < 0.017). Higher baseline OXT concentrations predicted more readmissions and fewer days to the first readmission (|Rho| > 0.185, P < 0.050) in male patients. This study provides novel and sex-separated insights into the role of the OXT system in AUD. We identified a mechanism that might underlie the sex-separated choice of beverage type and established that increased OXT concentrations during early abstinence predict a worse outcome in male patients with AUD.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Alcohol dependence; Alcohol use disorder; Alcoholic beverages; Alcoholism; Ethanol; Oxytocin; Patient readmission; Prospective studies